Popisi prebivalstva 1857 – 1931 - Blaj Hribar, Neja (Prispevki za novejšo zgodovino, 2022)
In the following article, the author focuses on the historical population censuses in the Habsburg Monarchy and the Kingdom of SHS/Yugoslavia. She begins by introducing the legislation and the census method and then analyses the individual censuses and census headings. The final part of the article is devoted to a critical review of the collection and analysis of census data. It explores what the new digital data processing methods allow for and focuses on the importance of methodology.
Keywords: Avstro-Ogrska; habsburška monarhija; Jugoslavija; Kraljevina SHS; Kranjska; podatkovne baze; popisi prebivalstva